High Serum Irisin Concentration Is Associated with More Disturbed Behavioural Eating Pattern in Adolescent Rhythmic Gymnasts - Liina Remmel; Jaak Jürimäe; Anna-Liisa Tamm; Priit Purge; Vallo Tillmann (Children)
Background/Objectives: There are strict demands on body weight and shape in highly trained adolescent female athletes, and they are in the highest risk group for the development of eating disorders. This study aims to compare the behavioural eating patterns between highly trained female adolescent athletes and untrained controls (UCs), and to describe the associations between behavioural eating patterns and different energy homeostasis hormones. Methods: A total of 33 rhythmic gymnasts (RGs), 20 swimmers (SWs), and 20 UCs (n = 20) that were 14 to 18 years old participated in this investigation. Anthropometric measurements, body composition, training volume, 3-consecutive-day energy intake, and different energy homeostasis hormones were measured. For the evaluation of the individual behavioural eating pattern, an eating disorders assessment scale (EDAS) questionnaire with different subscales was used. Results: The mean EDAS subscale of restrained eating score was significantly higher in the RG group compared to the UC group (17.2 ± 7.4 vs. 11.5 ± 5.8; p < 0.05). The EDAS total score (r = 0.380) and the subscale score of preoccupation with body image and body weight (r = 0.371) were both positively correlated (p < 0.05) with serum irisin concentrations in the RG group. Conclusions: In conclusion, female rhythmic gymnasts reported a more often restrained eating pattern than untrained controls, and their more disturbed behavioural eating pattern was associated with a higher serum irisin concentration.